The Impact of Implementing COBIT 2019 Framework on Reducing the Risks of e-Audit - Thabit H. Thabit (PROSPECTIVE RESEARCHES, 2023)
This research aims at clarifying the concept of COBIT2019 framework, its most important advantages, and public awareness level of its implementation benefits in IT environment, as well as clarifying the most important risks facing e-Audit to explain the potential impact of the COBIT2019 implementation on reducing the risks of e-audit. The researcher employs descriptive approach by sending equestionnaires to academics and auditors in Erbil - Iraq, and analyzing collected data by statistical tools using SPSS. He concludes that there is an average interest by responders in Erbil to implement COBIT2019 as an effective system in reducing e-audit risks, and the applying of eaudit through the efficient implementation of COBIT2019 can enhance the position of the audit profession as an important control tool. Main recommendations of this research can be the government should work to reduce the e-audit risks by enforcing all organizations to implement COBIT2019 framework, and it should encourage the applying of e-Audit in the organizations because that can be a good motivation to enhance the IT infrastructure in the country.